2003
DOI: 10.1038/sj.ijo.802225
|View full text |Cite
|
Sign up to set email alerts
|

Lower cognitive function in the presence of obesity and hypertension: the Framingham heart study

Abstract: OBJECTIVE:To determine the independent effects of obesity and hypertension on cognitive functioning. METHODS: Using a prospective design, male (n ¼ 551) and female (n ¼ 872) participants of the Framingham Heart Study were classified by presence or absence of obesity and hypertension based on data collected over an 18-y surveillance period. All subjects were free from dementia, stroke, and clinically diagnosed cardiovascular disease up to the time of cognitive testing. Statistical models were adjusted for age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
414
11
18

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(471 citation statements)
references
References 29 publications
28
414
11
18
Order By: Relevance
“…Adipose tissue is a potent source of peripheral IL-6 thought to account for approximately 30% of circulating levels (33). Further, greater BMI in middle and later life is associated with poorer cognitive function independently of age (52) and predicts temporal lobe and global brain atrophy, cognitive decline, and the incidence of dementia (35,(52)(53)(54)(55)(56). Animal studies also show that obesity is associated with impaired hippocampal LTP (57) and deficits in hippocampal-dependent learning and memory (58).…”
Section: Discussionmentioning
confidence: 89%
“…Adipose tissue is a potent source of peripheral IL-6 thought to account for approximately 30% of circulating levels (33). Further, greater BMI in middle and later life is associated with poorer cognitive function independently of age (52) and predicts temporal lobe and global brain atrophy, cognitive decline, and the incidence of dementia (35,(52)(53)(54)(55)(56). Animal studies also show that obesity is associated with impaired hippocampal LTP (57) and deficits in hippocampal-dependent learning and memory (58).…”
Section: Discussionmentioning
confidence: 89%
“…Em anos recentes, tem começado a ficar clara também a associação entre fatores de risco cardiovascular e distúrbios do desempenho cognitivo (Farmer et al, 1990;Elias et al, 2003).…”
Section: Introductionunclassified
“…A partir da classificação da gravidade de ICC de acordo com os critérios da New York Heart Association (NYHA), o comprometimento da memória, em especial de fixação e aprendizado (Harrington et al, 2000), nos pacientes com ICC nas classes funcionais (CF) I, II e III da NYHA vem sendo apontado consistentemente na literatura (Deary et al, 1991;Grubb et al, 2000;Glynn et al, 2002;Elias et al, 2003;Bennett e Sauve, 2003;Antonelli Incalzi et al, 2003). No caso de pacientes com ICC-grave (CF IV -NYHA), o prejuízo da cognição é mais intenso e global, incluindo déficits atencionais (Almeida e Flicker, 2001;Almeida e Tamai, 2001).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…35 A large body of epidemiological and clinical evidence in recent years has indicated that, rather than separate entities with distinct causes, VaD and AD share similar CVRFs. 36 Thus, several studies have suggested that, even in the absence of stroke, the incidence of AD is significantly influenced by the presence and severity of elevated blood pressure, [37][38][39] diabetes, 30,40 smoking, 41 and physical inactivity. 42 High cholesterol levels have been associated with increased risk of AD in a number of studies, but there are also negative reports, and these conflicting results are thought to be caused by different mediating effects of age, gender, and APOE genotype.…”
Section: Cardiovascular Risk Factors and Cognitive Declinementioning
confidence: 99%